The Effect of Empowerment, Planning Quality (KP) Apparatus Performance (KA) on Regional Development in the Municipal Government of Banjarbaru - Noorrahman, Firdaus; Yunani, Akhmad; Rizali, Rizali (Syntax Literate, 2021)
This research was conducted to determine the effect of empowerment, planning quality (KP) and apparatus performance (KA) simultaneously on regional development in the Banjarbaru City Government. This research approach uses a quantitative causal method. The data collection technique used a questionnaire. The population of this research is 103 people with random sampling technique and the research sample is 83 people. The data analysis technique used multiple linear regression analysis, F test and T test. The results obtained in the study indicate that the Empowerment of Apparatus (X1) on Regional Development (Y) sig 0.000 value. The sig value is smaller than the probability value of 0.05, or the value of 0.000 <0.05, then H1 is accepted and Ho is rejected. The variable X1 has a tcount of 4.296 with t table = 2.021. So tcount> ttable can be concluded that the variable X1 has a contribution to Y. Quality Planning (X2) on Regional Development (Y) sig 0.039. The sig value is smaller than the probability value 0.05, or the value 0.016 <0.05, then H2 is accepted and Ho is rejected. The variable X2 has a tcount of 2.590 with t table = 2.021. Apparatus Performance (X3) on Regional Development (Y) value of 0.002> 0.05, then H3 is accepted and Ho is rejected. The variable X3 has a tcount of 3,150 with ttable = 2,021. The results of the F test F count is 16,854 with a probability value (sig) = 0,000. Value of Fcount (16,854)> Ftable (3,10), and the value of sig. smaller than the probability value of 0.05 or the value of 0.000 <0.05; then H01 is accepted. Apparatus Empowerment (X1), Planning Quality (X2) and Apparatus Performance (X3), affect regional development (Y) with R Square of 0.393 = 39.3% on Regional Development, while 64.6%. The results of the dominant test of Apparatus Empowerment (X1) are more influential on regional development (Y) in the City Government of Banjarbaru with a value of 0.303 at the sig level of 0.000. So it can be explained that if the empowerment of the apparatus is good in the regions, the development of the Banjarbaru city will be even better.